Estimation of Power for Reversible Subtractors - V.Naga Lakshmi, E.; N.Siva Sankara Reddy, Dr. (International Journal of Engineering and Technology, 2018)
In recent years Reversible Logic Circuits (RLC) are proved to be more efficient in terms of power dissipation. Hence, most of the researchers developed Reversible logic circuits for low power applications. RLC are designed with the help of Reversible Logic Gates (RLG). Efficiency of the Reversible gates is measured in terms of Quantum cost, gate count, garbage output lines, logic depth and constant inputs. In this paper, measurement of power for RLG is done. Basic RLGs are designed using GDI technology and compared in terms of power dissipation. 1 bit Full subtractor is designed using EVNL gate [1] and also with TG& Fy [6] gates. The power dissipation is compared with 1 bit TR gate [5] full subtractor. Then 2 bit, 4 bit and 8 bit subtractors are designed and compared the powers. Proposed 4 bit and 8 bit full subtractors are dissipating less power when compared to TR gate 4 bit and 8 bit subtractors.